N. Muhindro Singh , N. Savino , M. Dhaneswar Singh , Hemant Kumar and A. Ameeta Devi - N. Muhindro Singh , N. Savino , M. Dhaneswar Singh , Hemant Kumar and A. Ameeta Devi, (Indian Journal of Extension Education, 2016)
The present study was carried out on 400 households, belonging to 4 blocks of Senapati district of Manipur during 2013-15. Senapati district was selected keeping in view of major concentration of tribals with highest pig population in the stateof Manipur. A sample of farmers comprising of 100 respondents from each block was selected for the present study.Locations had significant (P